Solriamfetol for Excessive Daytime Sleepiness in Parkinson's Disease: Phase 2 Proof‐of‐Concept Trial. Issue 10 (30th June 2021) - Videnovic, Aleksandar; Amara, Amy W.; Comella, Cynthia; Schweitzer, Paula K.; Emsellem, Helene; Liu, Kris; Sterkel, Amanda L.; Gottwald, Mildred D.; Steinerman, Joshua R.; Jochelson, Philip; Zomorodi, Katie; Hauser, Robert A.
Abstract: Background: Solriamfetol is approved (US and EU) for excessive daytime sleepiness (EDS) in narcolepsy and obstructive sleep apnea. Objectives: Evaluate solriamfetol safety/efficacy for EDS in Parkinson's disease (PD). Methods: Phase 2, double‐blind, 4‐week, crossover trial: adults with PD and EDS were randomized to sequence A (placebo, solriamfetol 75, 150, 300 mg/d), B (solriamfetol 75, 150, 300 mg/d, placebo), or C (placebo). Outcomes (safety/tolerability [primary]; Epworth Sleepiness Scale [ESS]; Maintenance of Wakefulness Test [MWT]) were assessed weekly. P values are nominal. Results: Common adverse events (n = 66): nausea (10.7%), dizziness (7.1%), dry mouth (7.1%), headache (7.1%), anxiety (5.4%), constipation (5.4%), dyspepsia (5.4%). ESS decreased both placebo (−4.78) and solriamfetol (−4.82 to −5.72; P > 0.05). MWT improved dose‐dependently with solriamfetol, increasing by 5.05 minutes with 300 mg relative to placebo ( P = 0.0098). Conclusions: Safety/tolerability was consistent with solriamfetol's known profile. There were no significant improvements on ESS; MWT results suggest possible benefit with solriamfetol in PD. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society